Safety and efficacy of SARS-CoV-2 vaccination in 1237 patients with primary Sjögren syndrome. - İNANÇ, GÜZİDE NEVSUN (My University, 2022)
Objective To investigate the safety and efficacy of SARS-Cov-2 vaccination in patients with primary Sjögren syndrome (pSS) due to scarcity of data in this population. Methods By the first week of May 2021, all Big Data SS Consortium centres patients who had received at least one dose of any SARS-CoV-2 vaccine were included in the study. The in-charge physician asked patients about local and systemic reactogenicity to collect SARS-CoV-2 vaccination data. Results The vaccination data of 1237 patients were received. A total of 835 patients (67%) reported any adverse events (AEs), including local (53%) and systemic (50%) AEs. Subjective symptoms (63%) were the most common local AEs, followed by objective signs at the injection site (16%), and general symptoms were the most commonly reported systemic AEs (46%), followed by musculoskeletal (25%), gastrointestinal (9%), cardiopulmonary (3%), and neurological (2%). In addition, 141 (11%) patients reported a significant worsening/ exacerbation of their pre-vaccination sicca symptoms and fifteen (1.2%) patients reported active involvement in the glandular (n=7), articular (n=7), cutaneous (n=6), pulmonary (n=2), and peripheral nervous system (n=1) domains due to post-vaccination SS flares. In terms of vaccination efficacy, breakthrough SARS-CoV-2 infection was confirmed after vaccination in three (0.24 %) patients, and positive anti-SARS-Cov-2 antibodies were detected in approximately 95% of vaccinated SS patients, according to data available. Conclusion Our data suggest that patients with pSS develop adequate humoral response and no severe AEs after SARS-CoV-2 vaccination and therefore raise no concerns about the vaccine’s efficacy or safety profile in this population.
Keywords: primary Sjögren syndrome; SARS-CoV-2 vaccination; Sjögren Big Data Consortium; adverse events; disease flare